The compressive strength and water absorption of sand brick containing lime and different percentage of RHA a partially sand replacement - Muhammad Nasoha, Mohd Rashid (2012)
One of the major elements in construction is brick. In Malaysia, the brick is commonly useful as a masonry wall. The improvement in the brick technology is important in reducing the cost of construction. The Rice Husk Ash (RHA) and lime is one of the elements in improving the strength of the brick as well as reducing the cost of brick. The RHA and lime can be used as the replacement of the sand where the cost of sand is increasing in market. The size of the RHA is less than the sand but it suitable to replace the sand in the brick. The strength of the brick that are containing the RHA and the lime is hoping can achieve the strength of the normal sand brick and can be used at the uncritical masonry in the construction. This study is aiming to determine the compressive strength and the water absorption of the brick that are replacing slightly the sand with RHA and lime. In this research, the brick size used is 117mm width x 75mm thickness x 215mm length. The result of compressive strength test shows the increments of strength of the brick rather than the normal sand brick. Instead of the increments of strength in the brick, there are reductions in the cost of making brick itself. Also the result of the water absorption test, the result shows the reduction of the absorption from the water that make the brick have more strength and not easily fragile.